Pengembangan Bahan Ajar Chatbot Berbasis Artificial Intelligence Materi Sistem Peredaran Darah Manusia Kelas V - Khusnul Istiqomah; Vidya Setyaningrum; Dwi Surya Atmaja (UIR Press, 2023)
This study aims to describe product development steps, quality results for the development of chatbot teaching materials, and student responses from the use of chatbot teaching materials on human circulatory system material. This research uses the Research and Development (R&D) method with a 4D model (define, design, development, dessimate). Product testing was carried out with 28 students of class V SD. The validation test was carried out by two material experts, two software experts, and two language experts. The result was that a value of 1 was obtained in the